Nanomaterial‐Boosted Tumor Immunotherapy Through Natural Killer Cells. Issue 12 (27th October 2022) - Zhan, Mengsi; Guo, Yunqi; Shen, Mingwu; Shi, Xiangyang
Abstract : Natural killer (NK)‐cell immunotherapy as an alternative to T‐cell immunotherapy has been widely used in clinical cell immunotherapy of various tumors. Despite the surprising findings, the widespread applications of NK cells are still limited by the insufficient expansion and short lifespan of adoptive NK cells in vivo, the poor penetration of NK cells in solid tumors, as well as the immunosuppressive tumor microenvironment that may cause the inactivation of NK cells. Fortunately, the emergence of nanomaterials provides many opportunities to address these vexing problems, thus overcoming the barriers faced by NK cells and promoting the tumor inhibitory efficacy of NK cells. Herein, the recent advances in the rational design of nanomaterials for boosting the NK cell‐based immunotherapy, mainly through enhancing NK cell engagement with tumors, boosting NK cell activation or expansion, as well as redirecting NK cells to tumor cells, are reviewed. Lastly, the design and preparation of next‐generation nanomaterials that aim to further boost the NK cell‐based immunotherapy are briefly discussed. Abstract : Recent advances in the design of nanomaterials for boosting the natural killer (NK) cell‐based immunotherapy are summarized. Nanomaterials can be designed to enhance NK cell engagement with tumors, boost NK cell activation or expansion, and redirect NK cells to tumor cells. The current challenges and future perspectives of nanomaterial‐based NK‐cell immunotherapy to further improve the tumor therapeutic efficacy are discussed.